PENGARUH PIJAT COMMON COLD TERHADAP GEJALA COMMON COLD PADA BALITA DI PUSKESMAS KAMPUNG BUGIS - Dwi Retna Ningrum; Mariyana, Mariyana; Yuniftri, Astri (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2025)
ABSTRACT The common cold is one of the most frequent upper respiratory tract infections among toddlers, characterized by symptoms such as cough, runny nose, fever, and irritability, which may interfere with comfort and reduce quality of life. Non-pharmacological management, such as massage therapy, is believed to reduce symptoms by improving circulation, relaxation, and immune stimulation. However, the effectiveness of massage in alleviating common cold symptoms in toddlers still requires further evidence. This study aimed to determine the effect of massage on reducing common cold symptoms among toddlers in the working area of Kampung Bugis Public Health Center in 2025. This research employed a quasi-experimental design with a pretest-posttest control group. A total of 30 toddlers who met the inclusion criteria were selected and divided into intervention and control groups. Data collection used an observation sheet assessing common cold symptoms including cough frequency, runny nose, fever, and sleep disturbances. Data analysis was conducted using the Wilcoxon test for within-group comparison and the Mann-Whitney test for between-group differences. The results showed a significant reduction in symptoms in the intervention group before and after massage, with a p-value of 0.000 (<0.05). No significant change was found in the control group (p = 0.143). Between-group comparison revealed a significant difference (p = 0.001), indicating that massage was effective in reducing common cold symptoms among toddlers. In conclusion, massage has a significant effect on reducing common cold symptoms in toddlers. It can be considered a safe, simple, and beneficial complementary non-pharmacological therapy to support child health. Keywords: Massage, Common Cold, Toddlers, Symptoms, Non-Pharmacological Therapy